Prevalence and co-existence of cardiometabolic risk factors and associations with nutrition-related and socioeconomic indicators in a national sample of Gambian women - Nicolai Petry (Nature Portfolio, 2021)
Abstract Cardiovascular diseases (CVD) are on the rise in Sub-Saharan Africa, and a large proportion of the adult population is thought to suffer from at least one cardiometabolic risk factor. This study assessed cardiometabolic risk factors and the contribution of nutrition-related indicators in Gambian women. The prevalence and co-existence of diabetes (elevated glycated hemoglobin (HbA1c ≥ 6.5%) or prediabetes (HbA1c ≥ 5.7% to < 6.5%), hypertension (systolic blood pressure ≥ 140 mmHg or diastolic blood pressure ≥ 90 mmHg), obesity (body mass index (BMI) ≥ 30.0) and inflammation (C-reactive protein (CRP) > 3 mg/L or alpha-1-acid glycoprotein (AGP) > 1 g/L) and the contribution of nutrition related and socioeconomic indicators were measured in non-pregnant women 15–49 years of age in the Gambia using data from a nationally representative cross-sectional stratified survey. Nationally, 54.5% (95% CI: 47.4, 61.4) of 1407 women had elevated HbA1c. Of these, 14.9% were diabetic and 85.1% were prediabetic. Moreover, 20.8% (95% CI 17.8, 20.0) of 1685 women had hypertension, 11.1% (95% CI 9.0, 13.7) of 1651 were obese and 17.2% (95% CI 5.1, 19.6) of 1401 had inflammation. At least one of the aforementioned cardiometabolic risk factor was present in 68.3% (95% CI 63.0, 73.1) of women. Obesity increased the risk of hypertension (aRR 1.84; 95% CI 1.40, 2.41), diabetes (aRR 1.91; 95% CI 1.29, 2.84), elevated HbA1c (aRR 1.31; 95% CI 1.14, 1.51) and inflammation (aRR 3.47; 95% CI 2.61, 4.61). Inflammation increased the risk of hypertension (aRR 1.42; 95% CI 1.14, 1.78). Aging increased the risk of hypertension, obesity and inflammation. Further, inadequate sanitation increased the risk for diabetes (aRR 1.65; 95% CI 1.17, 2.34) and iron deficiency increased the risk of elevated HbA1c (aRR 1.21; 95% CI 1.09, 1.33). The high prevalence of cardiometabolic risk factors and their co-existence in Gambian women is concerning. Although controlling obesity seems to be key, multifaceted strategies to tackle the risk factors separately are warranted to reduce the prevalence or minimize the risk of CVD.